Dynamic operation and control of a hybrid nanogrid system for future community houses - Chandrasena, R.; Shahnia, Farhad; Rajakaruna, Sumedha; Ghosh, Arindam (The Institution of Engineering and Technology, 2015)
A hybrid NanoGrid (NG) can be considered as the power supply system, for future community houses. In this study, the operation and control of an NG are presented. The NG consists of an AC bus and a DC bus, interconnected through a tie-converter (TC). All AC loads and distributed energy resources (DERs) of the community houses are connected to the AC bus while all their DC loads and DERs are connected to the DC bus. The NG has an adequate generation capacity to supply its loads in off-grid status as well as the capability to exchange power with the grid. The TC exchanges the power between two buses and regulates the voltage in both buses, in the case of off-grid operation. The NG dynamics, with the proposed structure and developed primary and secondary control algorithms are validated through extensive computer simulations in PSCAD/EMTDC.